Inovasi Perencanaan Pembangunan Berbasis Ekowisata: Sebuah Kajian Pustaka Sistematis: Ecotourism-based Development Planning Innovation: A Systematic Literature Review - Ul Inati; Salahudin (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
Tourism is an economic activity or a series of coordinated activities aiming at meeting individual needs related to leisure and movement of people. Tourism sector is well known as the sector that has the largest contribution for foreign exchange in Indonesia. Development planning itself can be said as an alternative to the government in carrying out the task of realizing a change in certain areas to be able to catch up with other regions. The application of innovation aims to develop a renewal involving several stakeholders. Ecotourism is an innovation that can be applied in promoting development planning in a real context. The purpose of this research is to find out the scientific trend about development planning ecotourism by using bibliometric analysis through the VOSviewer application. This research uses qualitative research with a literature review approach. The results consist of mapping and clustering the results of previous research in the form of image visualization media with network and density mapping. Projections of development planning by creating ecotourism-based innovations have been carried out in various parts of the world. The existence of development and its linkage with the tourism sector makes a positive impact on people's lives, especially rural communities. Limitations of this study is that only correlations on the existence of development in the tourism sector are presented.